MicroRNA-424 suppresses estradiol-induced cell proliferation via targeting GPER in endometrial cancer cells - Zhang, H; Wang, X; Chen, Z; Wang, W (Cellular and Molecular Biology, 2015)
Endometrial carcinoma (EC) is the most common gynecologic malignancy with increasing morbidity in recent years. MicroRNAs (miRNAs), a type of non-coding RNA, have been proven to be critical in the process of tumorigenesis. miR-424 has been reported to play a protective role in various type of cancer including endometrial carcinoma. It has been reported that high levels of estrogen increase morbidity of EC by promoting cell growth ability. The current research was designed to delineate the mechanism of miR-424 in regulating E2 (17Î²-estradiol)-induced cell proliferation in endometrial cancer. In this study, we confirmed that cell proliferation is increased significantly in E2-treated endometrial cancer cell lines. Moreover, miR-424 overexpression dramatically decreased E2-induced cell proliferation, indicating a pivotal role in endometrial cancer cell growth. In addition, the results suggest that miR-424 up-regulation inactivated the PI3K/AKT signaling, which was mediated by G-protein-coupled estrogen receptor-1 (GPER) in endometrial cancer. Furthermore, the luciferase report confirmed the targeting reaction between miR-424 and GPER. After transfection with the GPER overexpression vector into E2-induced endometrial cancer cells, we found that GPER significantly attenuated the inhibition effect of miR-424 in E2-induced cell growth in EC. Taken together, our study suggests that increased miR-424 suppresses E2-induced cell growth, and providing a potential therapeutic target for estrogen-associated endometrial carcinoma.